Effect of Phosmet Toxicity on Some Physiological Traits in Duckweed (Lemna gibba L.) - Şeyda Yılmaz; Ebru Bozlar; Muhittin Doğan (Aquatic Sciences and Engineering)
Pesticides, one of the chemicals that adversely affect the environment and human health, can have effects on non-target organisms due to their chemical properties and wide range of use. Therefore, in this study, the toxic effects of phosmet insecticides on Lemna gibba, an aquatic macrophyte, were determined as a non-target organism. The study was carried out in a climate cabinet under controlled conditions. It was determined that the photosynthetic pigments and total carbohydrate content of the macrophyte decreased with increasing phosmet concentration. Similarly, decrease in total phenolic contents were found. A significant and positive correlation between non-protein sulfhydryl groups (NP-SH) and H2 O2 contents may indicate their role in antioxidant defense mechanism. Besides, increases in malondialdehyde (MDA) and H2 O2 contents showed that phosmet toxicity caused oxidative stress in L. gibba tissues.